Prevalence of point mutations in the dihydrofolate reductase and dihydropteroate synthetase genes of Plasmodium falciparum isolates from India and Thailand: A molecular epidemiologic study - S. Biswas (2018)
Pyrimethamine-sulfadoxine (PS) is used as a second-line treatment for P. falciparum malaria patients who fail to respond to chloroquine. Resistance to these drugs has been shown to encode with point mutations in dihydrofolate reductase (DHFR) and dihydropteroate synthetase (DHPS) genes. Our aim was to assess the comparative rate of point mutation occurring in DHFR and DHPS genes among P. falciparum isolates from India and Thailand where the use of PS is at a different rate. We used the mutation-specific polymerase chain reaction (PCR) technique and mutation-specific restriction digestion to determine the prevalence of DHFR and DHPS gene mutations at codons 16, 51, 59, 108, 164 and at 436, 437, 581 and 613, respectively. In the 89 clinical isolates from India, in the case of the DHFR gene, we found 71 of S108N, 10 of N51I, 28 of C59R and four of I164L types. Among the 50 isolates from Thailand the rate of point mutations in the DHFR gene was higher at four codon positions. We found 47 of S108N, 18 of N51I, 23 of C59R and 12 of I164L types. None of the isolates from either country possessed the paired mutations S108T and A16V. Mutations of the DHPS gene were less frequent among the Indian isolates: 4.5% showed DHPS gene mutation, two of S436F, A437G, A613T and two of S436F, A613T; whereas 66% (33/50) of the Thai isolates had mutated at codons 436, 437, 581 and 613 which include 13 of S436F, 15 of A437G, 19 of A581G and 25 of A613S/T, ranging from single to quadruple mutant types. Among the Indian isolates, DHFR point mutations were very frequent and 85/89 had a wild type DHPS genetic profile. The pattern of mutations in the samples from Thailand was different, as most were associated with point mutations in DHFR arid DHPS genes.